2021
DOI: 10.1093/braincomms/fcab198
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific signatures of intrinsic hippocampal networks and regional integrity underlying cognitive status in multiple sclerosis

Abstract: The hippocampus is an anatomically compartmentalized structure imbedded in highly wired networks that are essential for cognitive functions. Hippocampal vulnerability has been postulated in acute and chronic neuroinflammation in multiple sclerosis, while the patterns of occurring inflammation, neurodegeneration or compensation have not yet been described. Besides focal damage to hippocampal tissue, network disruption is an important contributor to cognitive decline in multiple sclerosis patients. We postulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Increased functional connectivity between different brain regions as a compensatory mechanism for their more extensive GM loss was found in MMS compared to WMS in the study of Sanchis-Segura et al (26). In contrast, some other studies have found worse regional GM damage and related bigger network reorganization in WMS (32). By modeling single-subject intrinsic networks and quantifying subfield volumetric variations, sex-related differences in hippocampal vulnerability were found in a large 2 years longitudinal study of early RRMS (disease duration <5 years) patients compared to age matched controls (32).…”
Section: Sex-related Brain Gm Damagementioning
confidence: 86%
See 3 more Smart Citations
“…Increased functional connectivity between different brain regions as a compensatory mechanism for their more extensive GM loss was found in MMS compared to WMS in the study of Sanchis-Segura et al (26). In contrast, some other studies have found worse regional GM damage and related bigger network reorganization in WMS (32). By modeling single-subject intrinsic networks and quantifying subfield volumetric variations, sex-related differences in hippocampal vulnerability were found in a large 2 years longitudinal study of early RRMS (disease duration <5 years) patients compared to age matched controls (32).…”
Section: Sex-related Brain Gm Damagementioning
confidence: 86%
“…In contrast, some other studies have found worse regional GM damage and related bigger network reorganization in WMS (32). By modeling single-subject intrinsic networks and quantifying subfield volumetric variations, sex-related differences in hippocampal vulnerability were found in a large 2 years longitudinal study of early RRMS (disease duration <5 years) patients compared to age matched controls (32). MMS and WMS were matched for disease duration, cognitive scores, T2HL volumes and hippocampal volume.…”
Section: Sex-related Brain Gm Damagementioning
confidence: 94%
See 2 more Smart Citations
“…One limitation of this study is related to the lack of a control group of healthy subjects, which would have possibly allowed for a more clear differentiation between age-related and MS-specific DGM shape changes. In addition, DGM structures with an established central role for cognitive symptoms in MS( Ciolac et al, 2021 , Rocca et al, 2018 ) were not evaluated in our work. Future studies should consider including these structures, especially when cognitive disability in MS is being the main study focus.…”
Section: Discussionmentioning
confidence: 99%